Estimation of the aroma potential of Grapes - Concejero, B.; Hernández, P.; Ferreira, V.; Cacho, J. (Jornada de Jóvenes Investigadores del I3A, 2012)
Wine suffers important chemical transformations since the end of the fermentation process tillthe moment of consumption, whose object is the stabilization and maturation and fining ofwine organoleptic character. Within this context, the goal of the work is to understand thewine ageing process as a result of different enological variables involved in the formation ofsensory active molecules in wine. In particular, we aim to study the potential aromaticcomposition of wine as a function of its aroma precursor content along with the generationand degradation kinetics under the ageing conditions occurring in wine. For this purpose aseries of model solutions supplemented with, either flavor precursors extracted from differentgrape varieties, or with pure aromatic compounds, were submitted to an accelerated ageing(45ºC for 60 days) simulating maturation in the bottle. Volatile compounds derived from grapeflavor precursors were extracted by SPE and determined by GC‐MS after diferent times ofageing. The model wine spiked with the pure aromatic compounds was employed to monitorthe hydrolysis kinetics and compounds stability. On the other hand, in the solution spiked withflavor precursors, major differences in concentration were observed during the first week ofaccelerated ageing. Most compounds exhibited an initial significant increase and furthersteady decrease in their concentrations. Results from this experiment were employed toestablish a mathematical model to determine the number of aromatic compounds present atdifferent moments of the ageing process.